Medicaid expansion and provision of prescription contraception to Medicaid beneficiaries - Sumarsono, Andrew (Contraception, 2020)
INTRODUCTION: Medicaid expansion increased access to care, but longitudinal patterns of contraception use after the Medicaid expansion have not been described. METHODS: We evaluated the effects of Medicaid expansion on the amount and type of contraceptive prescriptions using the Medicaid State Utilization Dataset. RESULTS: Overall long-acting reversible contraception (LARC) use increased in both expansion and nonexpansion states. In a difference-in-differences analysis, states that expanded Medicaid had no appreciable increase in per-capita prescription rates of LARC (p = 0.26) or short-acting hormonal contraception (p = 0.09) when compared to nonexpansion states. DISCUSSION: The Medicaid expansion was not associated with a change in per-capita LARC or short-acting hormonal contraception use.